Correlation between nanomechanical properties and microstructural design concepts of bivalve muscle attachment sites - S. Hoerl; C. Micheletti; S. Amini; E. Griesshaber; K.-U. Hess; A.G. Checa; M. Peharda; W.W. Schmahl (Materials & Design)
Bivalves populate various marine environments and follow diverse lifestyles: attaching to substrates, burrowing into sediments or swimming in water. Their shells play a crucial role in the survival of organisms as they shield the soft tissue from external attacks and facilitate their respective lifestyles. Valve movement is controlled by one or two adductor muscles and the hinge. While the function and structure of adductor muscles can vary, the shell-muscle attachment develops the myostracum, a unique microstructural design. Sectioned parallel and perpendicular to the inner shell surface, we investigated myostracal and non-myostracal microstructures, textures and nanomechanical properties for three bivalve species: The burrowing Glycymeris pilosa, the sessile Chama arcana and the swimming Placopecten magellanicus.Analyses were conducted using electron backscatter diffraction measurements, laser confocal and backscatter electron imaging, nanoindentation testing and thermogravimetric analysis. We find that the myostracal microstructure is generated mainly through physical determinants, regardless of the bivalve lifestyle and adductor muscle structure. If aragonitic, we show that adjacent shell layers are used as templates for the formation of the myostracal microstructure and highlight how bivalves use the adjacent crystal arrangement to predetermine myostracal microstructure up to inner shell surfaces. Furthermore, this study demonstrates how myostracal layers exceed the hardness of the non-myostracal valves and that of geological aragonite, irrespective of grain size and morphology. Due to the anisotropy of aragonite, we show that aragonite c-axis orientation notably affects the hardness of crystals. The highest hardness is measured when indentation is normal to the shell surface in aragonite c-axes direction.